2019
DOI: 10.1007/s00125-018-4801-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular outcome trials of glucose-lowering medications: an update

Abstract: Three further cardiovascular (CV) outcome studies of glucose-lowering drugs (linagliptin, albiglutide and dapagliflozin) have recently been published, adding to the twelve earlier within-class studies. The linagliptin study (CARMELINA) recruited people with renal disease as well as prior CV events and confirms the overall CV safety (and other safety) of the dipeptidylpeptidase-4 (DPP4) inhibitors, with no heart failure risk associated with this agent. However, taken together with the findings from two previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 40 publications
1
46
0
4
Order By: Relevance
“…There have also been concerns regarding an increased risk of acute pancreatitis in post‐marketing studies, although a more recent meta‐analysis of randomised controlled trials did not find any association between GLP1 receptor agonist use and acute pancreatitis . The risk of pancreatitis is probably overstated at present, but the medication should be ceased permanently if pancreatitis develops, and GLP1 receptor agonists should be avoided in patients with a prior history of pancreatitis.…”
Section: Glucagon‐like Peptide 1 Receptor Agonistsmentioning
confidence: 99%
“…There have also been concerns regarding an increased risk of acute pancreatitis in post‐marketing studies, although a more recent meta‐analysis of randomised controlled trials did not find any association between GLP1 receptor agonist use and acute pancreatitis . The risk of pancreatitis is probably overstated at present, but the medication should be ceased permanently if pancreatitis develops, and GLP1 receptor agonists should be avoided in patients with a prior history of pancreatitis.…”
Section: Glucagon‐like Peptide 1 Receptor Agonistsmentioning
confidence: 99%
“…However, this risk increased to 3.7 or 3.8 if the subjects had diabetes and myocardial infarction or stroke simultaneously, suggesting increased mortality in patients with diabetes along with cardiometabolic multimorbidity. In addition, recent results from large cardiovascular outcome trials of novel anti-diabetic agents that control not only glucose but also multiple metabolic risk factors, reconfirms the importance of simultaneous intervention of multiple risk factors in patients with diabetes for the prevention of cardiovascular diseases [22]. Our study results showed that decreased renal function with eGFR <45 mL/min/1.73 m 2 resulted in a 3.4-fold increased mortality risk in patients with diabetes, which is the highest among the various comorbidities.…”
Section: Discussionmentioning
confidence: 93%
“…However, no dipeptidyl peptidase‐4 inhibitor drugs appear to reduce the risk of CVD in CVOT (but do not increase the risk) despite reducing HbA1c. Conversely, all sodium‐glucose transporter 2 inhibitor agents appear to reduce CVD risk to some extent in CVOT . These disparate outcomes suggest that a reduction of HbA1c is not sufficient to predict whether a drug to treat diabetes will lead to a reduction in hard CVD clinical endpoints.…”
Section: Maximising the Results Of Rcts In Pharmacoepidemiologymentioning
confidence: 99%
“…in CVOT. 77 These disparate outcomes suggest that a reduction of HbA1c is not sufficient to predict whether a drug to treat diabetes will lead to a reduction in hard CVD clinical endpoints. Thus, careful consideration of whether soft endpoints reported in clinical trials translate into clinically meaningful hard endpoints must always be given.…”
Section: A Note About Endpointsmentioning
confidence: 99%